Nonmarine Ostracoda as proxies in (geo‐)archaeology — A review. Issue 5 (3rd May 2022) - Quante, Ella; Pint, Anna; Frenzel, Peter
Abstract: Ostracods as bioindicators are extremely useful for reconstructing palaeoenvironment and palaeoclimate and can also indicate the provenance of sediments and materials, for example, in studies on ancient commercial networks. Ostracods are small crustaceans that live in almost all aquatic habitats, both natural and man‐made. Due to their calcitic carapace, they have high fossilization potential, and their use in geoarchaeology has been steadily increasing during the last decades. Their small size needs mean that only small volumes of sediment samples are needed, and species‐specific ecological tolerances and preferences allow detailed palaeoenvironmental reconstructions. Typical methods of their application are palaeoecological analyses of associations based on ecological information and taphonomy, morphometric variability and stable isotope and chemistry analyses of their shells. The present paper aims to present an overview of applications of non‐marine ostracods in (geo‐)archaeological research, recommending sampling and analytical techniques for addressing archaeological research questions on palaeoclimate, habitat and landscape changes, water availability and quality, land use and other anthropogenic impacts, the provenance of materials and commercial networks to promote the application of Ostracoda in geoarchaeology/environmental archaeology.